The Effect of Financial Literacy, Parents’ Social Economic and Student Lifestyle on Students Personal Financial Management - Novitasari, Dewiana; Juliana, Juliana; Asbari, Masduki; Purwanto, Agus (Department of Economics Education, Faculty of Economics, Universitas Negeri Semarang, 2021)
The purpose of this study was to analyze the effect of financial literacy, parents’ social economic and student lifestyle on students’ personal financial management. This study used quantitative methods and data analysis techniques of Structural Equation Modeling using SmartPLS 3.0 software. The research sample used a random sampling method. The data used primary data collected through a questionnaire. The number of returned and valid questionnaires was 220 samples. The data was processed by using SEM. The results of the study concluded that financial literacy had a significant effect on students’ personal financial management, student lifestyle had a significant effect on students’ personal financial management, and parents’ social economics had a significant effect on students’ personal financial management. The novelty of this research was the Correlation model of financial literacy, parents’ social economic and student lifestyle on students’ personal financial management. The results of this study can be a reference for further research that can be applied in other organizations.